The United Nations Role in Managing International Conflicts : A Case Study of East Timor - Rima Fauziah Ramadhani (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2026)
After the human rights violations that occurred in Dili (1991) and in the city of Liquica (1999), the União Democrática Timorense (UDT) and FRETILIN united to form the Council for Timorese National Resistance (CNRT) with the goal of continuing their struggle to achieve full independence, with Xanana Gusmão as its president. In May 1998, the fall of the Soeharto regime and the drastic political changes in Indonesia opened the door for international negotiations between Portugal, the United Nations, and Indonesia, allowing a referendum to be held for the people of East Timor, to decide whether they preferred autonomy or independence from Indonesia. International NGOs such as the East Timor Action Network (ETAN), the Catholic Church, and members of FRETILIN living in exile continued to raise the issue of East Timor’s independence. The proposal for East Timor’s independence gained international sympathy, primarily due to Indonesia’s illegal occupation in 1976 and the human rights violations, which were seen as leading to genocide.